Epigenetic reprogramming in periodontal disease: Dynamic crosstalk with potential impact in oncogenesis - Barros, Silvana P.; Fahimipour, Farahnaz; Tarran, Robert; Kim, Steven; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Justice, Anne; North, Kari (Wiley, 2020)
Periodontitis is a chronic multifactorial inﬂammatory disease associated with microbial dysbiosis and characterized by progressive destruction of the periodontal tissues. Such chronic infectious inflammatory disease is recognized as a major public health problem worldwide with measurable impact in systemic health. It has become evident that the periodontal disease phenotypes are not only determined by the microbiome effect, but the extent of the tissue response is also driven by the host genome and epigenome patterns responding to various environmental exposures. More recently there is mounting evidence indicating that epigenetic reprogramming in response to combined intrinsic and environmental exposures, might be particularly relevant due its plasticity and potential application towards precision health. The complex epigenetic crosstalk is reflected in the prognosis and progress of periodontal diseases and may also lead to a favorable landscape for cancer development. This review discusses epigenomics modifications focusing on the role of DNA methylation and pathways linking microbial infection and inflammatory pathways, which are also associated with carcinogenesis. There is a more clear vision whereas 'omics' technologies applied to unveil relevant epigenetic factors could play a significant role in the treatment of periodontal disease in a personalized mode, evidencing that public health approach should coexist with precision individualized treatment.
Keywords: epigenetic; inflammation; oncogenesis; periodontal disease